2015
DOI: 10.1002/chin.201509271
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Paenilarvins: Iturin Family Lipopeptides from the Honey Bee Pathogen Paenibacillus larvae.

Abstract: Paenilarvins: Iturin Family Lipopeptides from the Honey Bee Pathogen Paenibacillus larvae. -Isolation and structure elucidation of three novel iturin-type lipopeptides, paenilarvins A-C, are described. Paenilarvins A (Ia) and B (Ib) show strong antifungal activity against some rare human pathogenic species, cytotoxic activity against mouse fibroblast cell line L929 and significant toxicity against honey bee larvae. -(SOOD, S.; STEINMETZ, H.; BEIMS, H.; MOHR, K. I.; STADLER, M.; DJUKIC, M.; VON DER OHE, W.; STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 1 publication
0
25
2
Order By: Relevance
“…; Sood et al . ). Subsequently, the peritrophic membrane (PM) that protects the underlying gut epithelium is attacked by chitin‐degrading enzymes, one of which (PlCBP49) was recognized as a key virulence factor (Garcia‐Gonzalez et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Sood et al . ). Subsequently, the peritrophic membrane (PM) that protects the underlying gut epithelium is attacked by chitin‐degrading enzymes, one of which (PlCBP49) was recognized as a key virulence factor (Garcia‐Gonzalez et al .…”
Section: Introductionmentioning
confidence: 97%
“…These endospores germinate in the larval midgut lumen and massively proliferate before breaching the epithelium (Yue et al 2008). Paenibacillus larvae eliminates bacterial competitors in the larval gut by releasing nonribosomal peptides (Garcia-Gonzalez et al 2014a, 2014bHertlein et al 2014;Muller et al 2014;Sood et al 2014). Subsequently, the peritrophic membrane (PM) that protects the underlying gut epithelium is attacked by chitin-degrading enzymes, one of which (PlCBP49) was recognized as a key virulence factor (Garcia-Gonzalez et al 2014c).…”
Section: Introductionmentioning
confidence: 99%
“…These results led to a better understanding of the virulence differences and showed that the two genotypes follow different molecular strategies during the invasive phase of infection (Djukic et al ., ; Poppinga and Genersch, ). Differential production of several secondary metabolites was demonstrated (Garcia‐Gonzalez et al ., ; Hertlein et al ., ; Müller et al ., ; Sood et al ., ) including paenilamicin, which is produced by P. larvae ERIC II only and was shown to suppress the growth of bacterial competitors in the larval gut (Müller et al ., ; Müller et al ., ). A key virulence factor of both P. larvae ERIC I and ERIC II is Pl CBP49, a chitin‐degrading enzyme responsible for the destruction of the peritrophic matrix during infection (Garcia‐Gonzalez and Genersch, ; Garcia‐Gonzalez et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…, Sood et al. ), although the architecture of the gene clusters shows some variability (e.g., a stand‐alone FAAL in the puwainaphycin gene cluster). Aside from cyclic lipopeptides mentioned thus far, FAAL is involved in the synthesis of the linear lipopeptide microginin (designated as an adenylation domain for octanoic acid; Kramer ) and other cyanobacterial metabolites that contain a fatty acid moiety, namely jamaicamide, hectochlorin and hapalosin (designated as acyl‐ACP synthases in the respective publications; Edwards et al.…”
mentioning
confidence: 99%
“…Seven amino acids are added by NRPS modules and the nascent peptide is released and cyclized by a thioesterase domain (Te-domain). Iturin, bacillomycin, paenilarvin and puwainaphycin are synthesized analogously (Tsuge et al 2001, Koumoutsi et al 2004, Sood et al 2014, although the architecture of the gene clusters shows some variability (e.g., a stand-alone FAAL in the puwainaphycin gene cluster). Aside from cyclic lipopeptides mentioned thus far, FAAL is involved in the synthesis of the linear lipopeptide microginin (designated as an adenylation domain for octanoic acid; Kramer 2010) and other cyanobacterial metabolites that contain a fatty acid moiety, namely jamaicamide, hectochlorin and hapalosin (designated as acyl-ACP synthases in the respective publications; Edwards et al 2004, Ramaswamy et al 2007, Micallef et al 2015b.…”
mentioning
confidence: 99%